Objective preclinical measures for bone conduction implants - Wils, Irina; Geerardyn, Alexander; Putzeys, Tristan; Fierens, Guy; Denis, Kathleen; Verhaert, Nicolas (Frontiers in Neuroscience, 2024)
The study evaluates the accuracy of predicting intracochlear pressure during bone conduction stimulation using promontory velocity and ear canal pressure, as less invasive alternatives to intracochlear pressure. Stimulating with a percutaneous bone conduction device implanted in six human cadaveric ears, measurements were taken across various intensities, frequencies, and stimulation positions. Results indicate that intracochlear pressure linearly correlates with ear canal pressure (R² = 0.43, RMSE = 6.85 dB), and promontory velocity (R² = 0.47, RMSE = 6.60 dB). Normalizing data to mitigate the influence of stimulation position leads to a substantial improvement in these correlations. R² values increased substantially to 0.93 for both the ear canal pressure and the promontory velocity, with RMSE reduced considerably to 2.02 (for ear canal pressure) and 1.94 dB (for promontory velocity). Conclusively, both ear canal pressure and promontory velocity showed potential in predicting intracochlear pressure and the prediction accuracy notably enhanced when accounting for stimulation position. Ultimately, these findings advocate for the continued use of intracochlear pressure measurements to evaluate future bone conduction devices and illuminate the role of stimulation position in influencing the dynamics of bone conduction pathways.